"Scratch it out": carbon copy based paper devices for microbial assays and liver disease diagnosis. Issue 28 (25th June 2021) - Hasandka, Amrutha; Prabhu, Anusha; Prabhu, Akshata; Singhal, Hardik Ramesh; Nandagopal M. S., Giri; Shenoy, Revathi; Mani, Naresh Kumar
Abstract : Transfer of carbon copy material onto paper for hydrophobic barrier patterning and sensing applications. Abstract : We present a facile paper-based microfluidic device fabrication technique leveraging off-the-shelf carbon paper for the deposition of hydrophobic barriers using a novel "stencil scratching" method. This exceedingly frugal approach (0.05$) requires practically no technical training to employ. Hydrophobic barriers fabricated using this approach offer a width of 3 mm and a hydrophilic channel width of 849 μm, with an ability to confine major aqueous solvents without leakage. The utility of the device is demonstrated by porting a cell viability assay showing a limit-of-detection (LOD) of 0.6 × 10 8 CFU mL −1 and bilirubin assay with human serum showing a detection range of 1.76–6.9 mg dL −1 and a limit-of-detection (LOD) of 1.76 mg dL −1 . The intuitiveness and economic viability of the fabrication method afford it great potential in the field of point-of-care diagnostics geared towards providing testing infrastructure in resource-scarce regions globally.